2007
DOI: 10.1186/1742-4690-4-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chloroquine on reducing HIV-1 replication in vitro and the DC-SIGN mediated transfer of virus to CD4+T-lymphocytes

Abstract: Background: Chloroquine (CQ) has been shown to inhibit HIV-1 replication in vitro as well as in vivo and has been proposed to alter the glycosylation pattern of the gp120 envelope. These activities indicate that the compound can be used not only as an effective HIV-1 therapeutic agent but also as a modulator of the gp120 envelope protein structure enabling for the production of broader neutralizing Ab responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 40 publications
0
34
0
Order By: Relevance
“…CQ had an additive effect against HIV-1 when used in combination with other antiretroviral agents [155,156]. Naarding et al demonstrated that CQ reduced HIV-1 transmission to and replication in CD4 + T-lymphocytes [157]. Similarly, Martinson et al observed that CQ had a preventive role in HIV infection, reducing CD8 + T cell activation upon HIV replication [158].…”
Section: Chloroquine and Hydroxychloroquine And Hivmentioning
confidence: 99%
See 1 more Smart Citation
“…CQ had an additive effect against HIV-1 when used in combination with other antiretroviral agents [155,156]. Naarding et al demonstrated that CQ reduced HIV-1 transmission to and replication in CD4 + T-lymphocytes [157]. Similarly, Martinson et al observed that CQ had a preventive role in HIV infection, reducing CD8 + T cell activation upon HIV replication [158].…”
Section: Chloroquine and Hydroxychloroquine And Hivmentioning
confidence: 99%
“…Coronaviridae CoV Chloroquine in vitro [145][146][147] Picornaviridae Enteroviruses Chloroquine in vitro [160] Chloroquine in vitro/in vivo (mouse) [161] Filoviridae EBOV Chloroquine in vitro [142,143] in vivo [142] Artesunate, amodiaquine in vivo [58] Mefloquine in vitro [132] Retroviridae HIV Artemisinin in vitro [23] Doxycycline in vitro [23] Mefloquine, toremifene, posaconazole in vitro [132] Chloroquine in vitro [151,157,158] in vivo [155] Chloroquine, hydroxychloroquine in vitro [152][153][154]156] Phenuiviridae SFTSV Amodiaquine In vitro [163] Among the aryl-aminoalcohols, the use of MQ in the treatment of JCPyV infection has been extensive, although with contradictory outcomes. Among the aminoquinolines, both CQ and hydroxyCQ showed promising results in reducing the replication of some emerging viruses, such as DENV and ZIKV.…”
Section: Virus Family Virus Species Drug Type Of Study (Model) Referementioning
confidence: 99%
“…Renewed interest in chloroquine has emerged after recent reports of its effectiveness in reducing viral loads of HIV-1 (1,2). Despite its widespread use, chloroquine has a very narrow margin of safety.…”
mentioning
confidence: 99%
“…Nalidixic acid and chloroquine share structural features being essential for their antibacterial and antiparasitic activity, respectively. Apart from its well-known antimalarial effects [2][3][4], chloroquine exerts direct antiviral [5][6][7][8][9][10][11][12][13], antifungal [13][14][15][16], and antibacterial effects [13,[17][18][19][20]. Furthermore, chloroquine exhibits immunomodulatory activity [21][22][23][24][25] and was found to reverse P-glycoprotein (P-gp)-mediated multidrug resistance, thereby increasing the cytotoxicity of some antineoplastic agents [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%